SPYN: desenvolvimento e aplicações de um novo software para estudos de cristalografia por RMN - Silva, Jefferson Richard Dias da (2021)
Resumo em língua estrangeira: The results obtained by NMR-es are difficult to understand due to several factors such as: anisotropy, dipolar coupling and the need for high sample rotations. Thus, NMR-es has a certain dependence on theoretical calculations of the chemical shielding tensors for crossing with the experimental data. In this work, a graphic and intuitive software was developed to assist in NMR crystallography studies - the SPYN platform, in addition to structural aspects through quantum chemistry calculations. The four forms of lamivudines were elucidated experimentally by NMR-es, the calculations of the shielding tensors for both GIAO and GIPAW methods were with low error in relation to the experimental chemical shifts which shows the low values of average and median error , in addition the high correlation of Pearson and Kendall explain the coherence between theoretical and experimental chemical shifts. The calculations of QTAIM and NBO were performed using theory and basis set M062X/6-311 ++g** and showed all intra- and intermolecular interactions, as well as the relationship of the interatomic distance with the hydrogen bonding force. QTAIM has shown that there are interactions of hydrogen with sulfur for C and D structures, which in general are long bonds 3,41 $Å$ and 2,80 $Å$ respectively. We hope that the SPYN application can help the scientific community to make the calculation of chemical shielding tensors, conformational search and calculation of the boltzmann distribution easily and also that structural studies on lamivudine cocrystals help to develop new drugs.